Konservasi Moral dan Pembentukan Karakter Mahasiswa Melalui Pendidikan Karakter Bagi Fungsionaris Mahasiswa FISIP UNNES - Salam, Rudi; Sasea, Sanita Carolina; Saraswati, Ufi; Wahyuningsih, Nining; Qoriah, Umi (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
The phenomenon of the fading of students' politeness when interacting and communicating both to lecturers and parents as well as the community is a challenge for academics to improve it. Character education is very important for student functionaries as an example for other students. This research method uses a literature review that will review sources or works published in journals, books or papers. The results of the research are that in order for students to have noble morals, character education must be applied in universities. All lecturers as educators are responsible for fostering the morality and character of students. Students tend to imitate the attitudes and actions of teachers, so they make lecturers as role models, so they should provide a good example for students.